THE STUDENTS' LEARNING ACHIEVEMENT AFTER AND WITHOUT STUDYING ENGLISH IN ELEMENTARY SCHOOL - Gusri Emiyati Ali (JALL (Journal of Applied Linguistics and Literacy), 2020)
The Critical Period Hypothesis by Lenneberg (1976)  states that ages 2 to 12 are ideal ages for achieving foreign language skills such as a native speaker. Based on this hypothesis, the perfect time for children to learn English as a foreign language is in elementary school. Meanwhile, Indonesian government policy through the 2013 curriculum does not require children in primary schools to learn English. Therefore, this study aimed to compare the English learning achievement of students between those who studied and those who did not study English in elementary school. This research is important to be conducted since it can be a reference for the Indonesian government in developing English language teaching and learning policy in elementary schools.  The sample of this research consisted of two groups selected through a purposive sampling technique. They were the groupS of students who studied and who did not study English in elementary school. Data were grouped, presented, and then compared. The results showed that students who studied English in elementary school had better English learning achievement than students who did not study English in elementary school. It is recommended for further related researches to consider many factors those can be influencing the students' English learning achievements such as the English teaching and learning method used by the educators in high school and university, attitudinal factor, and the learning environment.